Emotional Responses Toward a New Research Policy Among Academics in a Chinese University - Lu, Hua; Zhang, Xiaorong (Frontiers in Psychology, 2021)
Teacher emotion has received prominent attention in the field of education as they are closely related to teacher identity and teachers’ well-being. While many previous studies have taken teachers’ emotions in teaching as their research focuses, this study investigated university English as a foreign language (EFL) teacher-researchers’ emotions and emotion regulation strategies in research in the context of a new research policy. One-on-one semi-structured interviews were conducted with seven EFL teacher-researchers at a Chinese university which implemented China’s new research policy of breaking the “five-only”, supplemented by the analysis of narrative frames and the institutional research documents. The data revealed that university EFL teacher-researchers experienced wide-ranging and diverse emotions at the micro-level of research, the meso-level of the institutional system, and the macro-level of national policy, with different attitudes towards the new research policy. They also employed multiple strategies of antecedent-focused and response-focused approaches to regulate emotions in research. This study helps unpack the complexity of emotions experienced by university teachers in research, and also calls for the attention of stakeholders to pay to the emotions and well-being of university EFL teachers.